SYNTHESIS AND STUDY OF ANTIOXIDANT ACTIVITY OF [(1-ARYL-5-FORMYL-1H-IMIDAZOLE-4-IL)THIO]PROPIONIC ACIDS - A. O. Palamar; A. M. Grozav; V. O. Chornous; I. M. Yaremiy; M. V. Vovk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
Introduction. Derivatives of imidazole belong to the promising group of compounds for antioxidant activity study, due to the series of recent publications. This is defined by special features of their structure, specific reactivity and significant potential of pharmacological action. Earlier during process of looking for new antioxidants we studied significant amount of imidazole derivatives, among which the [(1-aryl-5-formylimidazole-4-il)thio]acetic acids structurally modified by the formyl group and thioacetic acid fragment, are especially worth noting.